2016
DOI: 10.1111/bjh.14112
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles in sickle cell anaemia: promise and pitfalls

Abstract: Blood from patients with sickle cell disease contains microparticles (MP) derived from multiple cell sources, including red cells, platelets, monocytes and endothelial cells. MPs are of great interest because of their disease associations, their status as promising biomarkers, and the intercellular communications they mediate. To illustrate the likelihood of their relevance in sickle cell disease, we discuss the nature of MP, their profiling in sickle disease, some caveats relevant to their detection, their ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 119 publications
(168 reference statements)
3
57
0
Order By: Relevance
“…Furthermore the pre-analytical and analytical procedures that we used were also different. These two technical steps are well known critical factors impacting MP pattern, quantitatively and qualitatively [26]. Despite undertaken standardization attempts [51,52], no consensus for flow-cytometry analysis of MPs has emerged up to now [26] leading to different protocols and doubts on the most accurate strategy to be used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore the pre-analytical and analytical procedures that we used were also different. These two technical steps are well known critical factors impacting MP pattern, quantitatively and qualitatively [26]. Despite undertaken standardization attempts [51,52], no consensus for flow-cytometry analysis of MPs has emerged up to now [26] leading to different protocols and doubts on the most accurate strategy to be used.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that MPs originated from sickle RBCs may trigger coagulation, increase the production the production of radical oxygen species by endothelial cells, induce erythrocyte adhesion to endothelial cells and endothelial cell apopotosis, as well as, trigger renal vaso-occlusive crisis in a sickle mouse model [2426]. Furthermore, several studies also supported a role of MPs in the occurrence of several complications in patients with SCA [15,2728].…”
Section: Introductionmentioning
confidence: 99%
“…This is also correct. Published data evidence the involvement of oxidative stress (79,100,105,108,113,115,116,121,123,132,134,135), inflammation (9, 22, 27, 32, 101, 105-108, 115, 124-127, 134), dyslipidemia (135)(136)(137)(138), microparticles (89,122,123,139), and vasoactive peptides (110,111,(140)(141)(142)(143). These additional pathways (depicted in Figure 2) are potentially additive or synergistic to intravascular hemolysis-like mechanisms.…”
Section: Controversies Regarding the Hyperhemolysis Modelmentioning
confidence: 99%
“…Ferric and ferryl forms of hemoglobin produced in SCD and other forms of hemolysis are highly reactive in promoting oxidation (119)(120)(121). Hemolysis also produces red cell microparticles that can deliver toxic heme to endothelial cells (122,123). Heme species appear to activate innate immune sterile inflammation pathways through TLR4 and NALP inflammasome signaling (104,105,124,125).…”
Section: Evidence Linking Cell-free Hemoglobin To Scd Complicationsmentioning
confidence: 99%
“…In addition, immunologic or genetic interventions targeting endothelial protein C receptor (EPCR), activated protein C (APC), or thrombin also blunted the enhanced microvascular thrombosis [50]. Furthermore, microparticles (MPs) derived from RBCs and platelets may also influence SCD pathobiology especially maintaining its hypercoagulable state through activation of FXI dependent coagulation pathways [97]. …”
Section: Inflammation and Coagulation/thrombosis Cross-talk In Scdmentioning
confidence: 99%